L'immigration italienne - Ramirez, Bruno (Critère, 1982)
issued: 1982-21-00
Keywords: Italiens

Les Italiens au Québec - Painchaud, Claude; Poulin, Richard (Asticou / Critiques, 1988)
Keywords: Italiens

La recherche sur les Italiens du Québec - Ramirez, Bruno (Questions de culture, 1982)
Keywords: Italiens

Les Québécois d'origine italienne. Une longue histoire - Linteau, Paul-André (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Italiens

L'Église catholique et la communauté italienne de Montréal - Énard, Anne-Marie (Le facteur religieux dans la vie publique canadienne, 1980)
Keywords: Italiens

Stratégies migratoires et pratiques communautaires: les Italiens du Frioul - Peressini, Mauro (Recherches sociographiques, 1984)
issued: 1984-09/1984-12
Keywords: Italiens

Les Italiens de Montréal: l'adaptation dans une société pluraliste - Boissevain, Jeremy (Information Canada, 1971)
Keywords: Italiens

Migration, famille et communauté: les Italiens du Frioul à Montréal 1945-1980 - Peressini, Mauro (Université de Montréal, 1990)
Keywords: Italiens

Culture vinique et pathologies éthyliques chez les italiens de Montréal: étude exploratoire - Cardinal, Nicole (Université de Montréal, 1984)
Keywords: Italiens

Étude d'un mouvement migratoire: l'immigration italienne au Québec (1931-1971) - Malpas, Nicole (Université de Montréal, 1984)
Keywords: Italiens

Immigrants italiens dans l'espace social et culturel montréalais. Une synthèse historique - Ramirez, Bruno (Histoires d'immigrations à Montréal, 2014)
Keywords: Italiens

Conflits d'identité et d'allégeance. La propagande du consulat italien à Montréal dans les années 1930 - Perin, Roberto (Questions de culture, 1982)
Keywords: Italiens

Sujets et identités multiples: analyse des histoires de vie d'un groupe d'immigrants italiens à Montréal - Peressini, Mauro (Université de Montréal, 1991)
Keywords: Italiens

Rapports familiaux chez les Italiens du Québec - Ramirez, Bruno (Critère, 1982)
Keywords: Famille; Italiens

Conflit de culture et criminalité des Italiens à Montréal - Ribordy, François Xavier (Université de Montréal, 1970)
Keywords: Criminalité; Italiens

Langue et identité chez les Québécois d’ascendance italienne - Fortier, Anne-Marie (Sociologie et sociétés, 1992)
issued: 1992-23-00
Keywords: Italiens; Langue

Histoire comparée de l’action politique au sein des communautés italiennes au Québec et en Suisse de 1945 à 1985 - Guerrera, Marco (Université de Montréal, 2003)
Keywords: Italiens

Fascisme et communauté italienne de Montréal d'après L'Italia Nuova - Laplante, Jacinthe (Université de Sherbrooke, 2008)
Keywords: Idéologies; Italiens

Le fascisme et les Italiens à Montréal: une histoire orale, 1922-1945 - Salvatore, Filippo (Guernica, 1995)
Keywords: Idéologies; Italiens

Le processus identitaire dans le soccer chez les italiens de Montréal - Spadari, Luigi (Université de Montréal, 1998)
Keywords: Italiens; Soccer

Le Débat linguistique au Québec. La communauté italienne et la langue d'enseignement - Taddeo, Donat J.; Taras, Raymond C. (Presses de l'Université de Montréal, 1987)
Keywords: Italiens; Langue

Pays et patries: Mariages et lieux d'origine des Italiens de Montréal, 1906-1930 - Taschereau, Sylvie (Université de Montréal, 1987)
Keywords: Italiens; Mariage

Pays et patries: mariages et lieux d'origine des Italiens de Montréal, 1906-1930 - Taschereau, Sylvie (Université du Québec à Montréal, 1984)
Keywords: Italiens; Mariage

Espaces ethniques et question linguistique au Québec: à propos des communautés italienne et portugaise - Da Rosa, Victor M. P.; Poulin, Richard (Canadian Ethnic Studies / Études ethniques au Canada, 1986)
Number: 2
Keywords: Italiens; Portugais

Le vocabulaire de disponibilité trilingue des jeunes montréalais qui ont l'italien comme langue au foyer - Villata, Bruno (Université Laval, 1985)
Keywords: Italiens; Langue

Par monts et par vaux. Migrants canadiens-français et italiens dans l’économie nord-atlantique, 1860-1914 - Ramirez, Bruno (Boréal, 1991)
Keywords: Italiens; Travail

Étude sur le rôle de l'Église dans l'intégration des immigrés d'origine italienne dans la société montréalaise - Castelli, Giuseppe (Université de Montréal, 1980)
Keywords: Italiens; Églises

Réminiscences italiennes - Létourneau, Isabelle (Continuité, 2001)
issued: 2001-21-00
Keywords: Italiens; Petite-Italie (quartier); Quartiers

Saint-Léonard, banlieue italienne: anatomie d'une mutation - Pazzi, Lara (Université du Québec et Institut national de la recherche scientifique, 2012)
Keywords: Italiens; Quartiers; Saint-Léonard

De la Toscane au Canada, les statuaires italiens - Tremblay, Marc Alain; Carli-Trudeau, Jocelyne F. (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Arts sacrés; Italiens; Sculpture

Le concept de la sécurité nationale et les atteintes aux droits de la personne: les Italiens du Québec entre 1939 et 1945 - Le Comte, Marie (Université de Montréal, 1982)
Keywords: Italiens; Prisons

Quartier ethnique et propriété foncière: le cas de la communauté italienne de Montréal - Laplace, Gérard (Université de Montréal, 1984)
Keywords: Italiens; Logement; Quartiers

"La Sosta dello Spirito": autocritique - relance d'une rubrique de caractère religieux et en langue italienne au poste de radio C.F.M.B. 1410 à Montréal - Giuseppe, Castelli (Université de Montréal, 1975)
Keywords: Italiens; Radio

Essai de définition: les sculpteurs, statuaires et ornemanistes italiens à Montréal: de 1862 à 1880 - Vignola, Luce (Université du Québec à Montréal, 1996)
Keywords: Artisans; Italiens; Sculpture

Le comportement de consommation artistique et culturel des groupes ethniques à Montréal, le cas des Portugais, des Maghrébins et des Italiens - Paiement, Isabelle (Université du Québec à Montréal, 2000)
Keywords: Italiens; Maghrébins; Portugais

Les premiers Italiens de Montréal: l'origine de la Petite Italie du Québec - Ramirez, Bruno (Boréal Express, 1984)
Keywords: Italiens; Petite-Italie (quartier); Quartiers

Entre rupture et transmission: les pratiques alimentaires italiennes autour du marché Jean-Talon - Masson-Labonté, Amélie; Gagnon, Marie-Anne (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Alimentation; Italiens; Jardins; Marchés

La communauté italienne de Montréal en 1901 - Tonietto, Manon (Université du Québec à Montréal, 2004)
Keywords: Italiens; Quartiers; Saint-Jacques; Saint-Laurent (quartier)

Ethnicité, culture et société globale: le discours de leaders d'origine haïtienne, italienne, juive et libanaise de la région de Montréal - Therrien, Marthe (Université du Québec à Montréal, 1993)
Keywords: Haïtiens; Italiens; Juifs; Libanais

Memoria e riconoscimento nella narrazione filmica degli italiani di Montréal - Ramirez, Bruno (À l'italienne. Narrazioni dell'italianità dagli anni Ottanta a oggi, 2018)
Keywords: Cinéma; Italiens

La letteratura dell'emigrazione italo-canadese di Montréal - Tedeschi, Antonio (Université McGill, 2000)
Keywords: Italiens

L'insegnamento dell'italiano a Montreal verso il Duemila. Insegnamento e apprendimento al livello post-secondario in un contesto plurilingue - Picciano, Giovanna A. (Université McGill, 1997)
Keywords: Italiens; Langue

Languages in Contact: Error Analysis of Italian Childrens' Compositions in a Multilingual Context - Samperi Mangan, Jacqueline (Université McGill, 1991)
Keywords: Enfants; Italiens; Langue

Les catholiques du Québec et le fascisme italien (1929-1939) - Arcand, Robert (Université de Sherbrooke, 1986)
Keywords: Idéologies

Guido Nincheri: le savoir-faire de la Renaissance italienne à Montréal - Busseau, Laurent (Histoire Québec, 2017)
Number: 4
Keywords: Arts sacrés; Peinture; Vitraux; Églises

Le triomphe de l’opéra italien à Montréal, de l’union des Canadas à la Grande Guerre - Barrière, Mireille (Cap-aux-Diamants, 2016)
issued: 2016-23-00
Keywords: Opéra; Théâtre Royal

The Education of Italians in Montreal, 1895 to 1960 - Gadler, Yves Carmelo Luciano (Université McGill, 1994)
Keywords: Italiens

Destination: Montréal: l'étude de l'émigration en provenance de Casacalenda (Molise, Italie) - Malpas, Nicole (Cahiers québécois de démographie, 1997)
issued: 1997-23-00
Keywords: Italiens

The Italians of Quebec - Linteau, Paul-André (Boundaries of Identity: A Quebec Reader, 1992)
Keywords: Italiens

Gli Italiani in Canada - Vangelisti, Guglielmo F. S. (Chiesa Italiana di N. S. Della Difesa, 1955)
Keywords: Italiens

The Italians of Montreal: From Sojourning to Settlement, 1900-1921 - Ramirez, Bruno; Del Balso, Michael (Les Editions du Courant, 1980)
Keywords: Italiens

The Italians of Montreal: From Sojourning to Settlement, 1900-1921 - Ramirez, Bruno; Del Balso, Michael (Little Italies in North America, 1981)
Keywords: Italiens

Processus migratoire, communauté et bourgeoisie italo-québécoise - Painchaud, Claude (Université du Québec à Montréal, 1982)
Keywords: Italiens

Gli Italiani di Montreal : Note e Profili - Mingarelli, Giosafat (Jos) (Centro Italiano Attivita Commerciali-Artistiche, 1980)
Keywords: Italiens

Gli Italiani di Montreal. Note e Profili - Mingarelli, Giosafat (Jos) (Centro Italiano Attivita Commerciali-Artistiche, 1967)
Keywords: Italiens

The Italians of Quebec: Key Participants in Contemporary Linguistic and Political Debates - Linteau, Paul-André (Arrangiarsi. The Italian Immigration Experience in Canada, 1989)
Keywords: Italiens

The Italians of Montreal: Social Adjustment in a Plural Society - Boissevain, Jeremy (Arno Press, 1975)
Keywords: Italiens

The Italians of Montreal: Social Adjustment in a Plural Society - Boissevain, Jeremy (Information Canada, 1971)
Keywords: Italiens

Italiani in Canada: il caso di Montreal - Farnocchia, F. (Bolletino della Societa Geographica Italiana, 1981)
Number: 10
Keywords: Italiens

The Process of Integration of Immigrants: the Case of Italians in Montreal - Duce, Graciela E. (Université de Montréal, 1977)
Keywords: Italiens

The Pre-Baptism Instruction of Italian Immigrants at Our Lady of Pompei Parish in Montreal - Fugolo, Joseph (Université de Montréal, 1980)
Keywords: Italiens

Acculturation and Consumption Behaviour of Italian-Canadians in Montreal - Reedijk, Robert (Université Concordia, 1991)
Keywords: Italiens

The Influence of Culture on Pro-Environmental Activities: Comparing English, French and Italian Canadians - Qian, Zhonglian Cindy (Université Concordia, 2001)
Keywords: Italiens

Ethnicité et idéologie: le cas des italophones de Montréal - Oriolo, Stefano (Université Laval, 1990)
Keywords: Italiens

Les Italo-Québécois: acteurs et enjeux des débats politiques et linguistiques au Québec - Linteau, Paul-André (Studi emigrazione/ Études migrations, 1987)
Number: 86
Keywords: Italiens

Montreal's Italians and the Socio-Economy of Settlement, 1900-1930: Some Historical Hypotheses - Ramirez, Bruno (Urban History Review / Revue d'histoire urbaine, 1981)
Number: 1
Keywords: Italiens

Constructing Italian Ethnicity: A Comparative Study of Two Italian Language Newspapers in Australia and Canada, 1947-1957 - Iuliano, Susanna (Université McGill, 1994)
Keywords: Italiens

Aux sources d'un réseau migratoire: Casacalenda-Montréal, 1861-1931 - Malpas, Nicole (Université catholique de Louvain, 1995)
Keywords: Italiens

Italian Identity in Montreal: Issues of Intergenerational Ethnic Retention - De Martinis, Lucio (Université McGill, 2005)
Keywords: Italiens

Family, Paesani and Networks: Politics and Economy of Montreal Italians - Aramaki, Michiko (Université McGill, 1994)
Keywords: Italiens

Une communauté singulière. Les Pesaresi de Montréal - Perin, Roberto (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Italiens

Dal Mediterraneo all’Atlantico: ricordi di migrazione nella Montréal del secondo dopoguerra - Piraro, Sergio (Italian Canadiana, 2021)
Keywords: Italiens

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

Destination, Housing and Quality of Life in the Migrant Experience from Larino (Molise, Italy) to Milano and Montreal - Fainella, John G. (Université McGill, 1996)
Keywords: Italiens; Logement

Actor or Victim? Mario Duliani and His Internment Narrative - Perin, Roberto (Enemies Within: Italians and Other Internees in Canada and Abroad, 2000)
Keywords: Guerre; Italiens

Des Italo-Belges au Canada: résultats d'une première enquête - Morelli, Anne (Les immigrants préférés: Les Belges, 1999)
Keywords: Belges; Italiens

The Internment of Italian Canadians - Bruti Liberati, Luigi (Enemies Within: Italians and Other Internees in Canada and Abroad, 2000)
Keywords: Italiens; Prisons

Fascism and the Italians of Montreal: an Oral History, 1922-1945 - Salvatore, Filippo (Guernica, 1998)
Translators: _:n17371
Keywords: Idéologies; Italiens

Workers Without a Cause: Italian Immigrant Labour in Montreal, 1880-1930 - Ramirez, Bruno (Arrangiarsi. The Italian Immigration Experience in Canada, 1989)
Keywords: Italiens; Travail

Ethnicity on Trial: The Italians of Montreal and the Second World War - Ramirez, Bruno (On Guard for Thee: War, Ethnicity, and the Canadian State, 1939-1945, 1988)
Keywords: Guerre; Italiens

Italian Immigrant Women in Post-War Montreal - Atri, Josephine (Université Concordia, 1980)
Keywords: Femmes; Italiens

The Social Structure of the Italian and Ukrainian Communities in Montreal, 1935-1937 - Bayley, Charles M. (Université McGill, 1939)
Keywords: Italiens; Ukrainiens

The Means and Modes of Living of European Immigrants in Montreal - Gibbard, Harold A. (Université McGill, 1934)
Keywords: Finlandais; Italiens

Choix linguistiques, changements et alternances de langue: les comportements multilingues des italophones de Montréal - Labrie, Normand (Université Laval, 1989)
Keywords: Italiens; Langue

Italian Immigrant Women and Literacy: A Case Study - Constantino, Patricia (Université Concordia, 2001)
Keywords: Femmes; Italiens

Ethnicity and Housing Adaptation: the Italians in Montreal - Fainella, John G. (Université McGill, 1986)
Keywords: Italiens; Logement

''Tutti a Tavola!'' Feeding the Family in Two Generations of Italian Immigrant Households in Montreal - Cancian, Sonia (Edible Histories, Cultural Politics: Toward a Canadian Food History, 2012)
Keywords: Alimentation; Italiens

Intra-Ethnic Differences of the Perceptions of Aged Italian Women in Receiving Care - Bonar, Rita Aguzzi (Université McGill, 1993)
Keywords: Femmes; Italiens

From Acculturation to Integration. The Political Participation of Montréal's ltalian-Canadian Community in an Urban Context (1945-1990) - Ricci, Amanda (Université de Montréal, 2009)
Keywords: Féminisme; Italiens

Migration, Settlement, and Television: The Montreal’s Teledomenica Experience - Ramirez, Bruno (Voices in Italian Americana, 2010)
Number: 1
Keywords: Italiens; Télévision

On the Move: French-Canadian and Italian Migrants in the North Atlantic Economy, 1860-1914 - Ramirez, Bruno (McClelland and Stewart, 1991)
Keywords: Italiens; Travail

Les Italo-Montréalais [sic] et leur histoire (1ère partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2019)
issued: 2019-22-00
Keywords: Italiens; Travail

Montreal's King of Italian Labour: A Case Study of Padronism - Harney, Robert F. (Labour / Le travailleur, 1979)
Keywords: Cordasco; Antonio; Italiens

Brief Encounters: Italian Immigrant Workers and the CPR, 1900-30 - Ramirez, Bruno (Labour / Le travailleur, 1986)
issued: 1986-21-00
Keywords: Canadien Pacifique; Italiens

Italian Art and Artists in Nineteenth-Century Quebec: A Few Preliminary Observations - Lacroix, Laurier (Arrangiarsi. The Italian Immigration Experience in Canada, 1989)
Keywords: Italiens; Peinture; Sculpture

Institutional completeness, ethnic organizational style and the role of the state: the Jewish, Italian and Greek communities of Montreal - Rosenberg, Michael; Jedwab, Jack (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1992)
Number: 3
Keywords: Grecs; Italiens; Juifs

Families, Lovers and their Letters: Italian Postwar Migration to Canada - Cancian, Sonia (University of Manitoba Press, 2010)
Keywords: Famille; Femmes; Italiens

Les Italo-Montréalais [sic] et leur histoire (suite et fin) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2019)
issued: 2019-23-00
Keywords: Guerre; Idéologies; Italiens

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

Pressure Group Politics: Case Study of the St. Leonard Schools Crisis - Parisella, John E. (Université McGill, 1971)
Keywords: Italiens; Saint-Léonard (crise de)

Leonardo da Montreal: The Rhetoric of Italianità and the Canadian Post-Nation - Fratiloiu, Raluca Maria (Université Concordia, 2006)
Keywords: Centre Leonardo Da Vinci; Italiens

Montreal E Il Suo Certificato Di Nascita, 1535-1985: Ommagio Alla Nostra Citta Nel Suo 450mo Anno Di Nascita/Montréal et son certificat de naissance, 1535-1985: à notre ville à l'occasion de son 450ième anniversaire de naissance - Menchini, Camillo M. (C. Menchini, 1985)
Keywords: Cartier; Jacques; Hochelaga; Italiens

Italian Influences on the Cultural Life of Old Montreal - Goggio, Emilio (Canadian Modern Language Review, 1952)
1952-23-00
Keywords: Italiens; Quartiers; Vieux-Montréal

When Nationalisms Collide: Montreal's Italian Community and the St. Léonard Crisis, 1967-1969 - D'Andrea, Giuliano E. (Université McGill, 1989)
Keywords: Italiens; Saint-Léonard (crise de)

Du Centro Donne Italiane di Montréal aux Donne d’Acciaio. - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2023)
Keywords: Ahuntsic; Femmes; Féminisme; Italiens

Une communauté en transition: la Petite Italie de Montréal - Del Balso, Michael (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
issued: 2002-21-00
Keywords: Italiens; Petite-Italie (quartier); Quartiers

Cultivating Heroes: From Dante and Caboto to Mussolini, the Public Art of Montreal's Italians in the 1920s-1930s - Carlevaris, Anna Maria (Université Concordia, 2004)
Keywords: Italiens; Monuments; Peinture; Sculpture

Italianité, conflit linguistique et structure du pouvoir dans la communauté italo-québécoise - Painchaud, Claude; Poulin, Richard (Sociologie et sociétés, 1983)
Number: 2
Keywords: Anglophones; Francophones; Italiens; Langue

"My Love, How Different Life Is Here..." A Young Italian Woman's Impressions of Postwar Montreal - Cancian, Sonia (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Femmes; Italiens; Langue; Travail

Bienvenue dans la Petite-Italie de Montréal - Taschereau, Sylvie (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Italiens; Petite-Italie (quartier); Quartiers

A Fractured Identity: The 1980 Referendum and the Italians of Montreal - Pannunzio, Anthony (Université McGill, 2022)
Keywords: Indépendantisme; Italiens; Nationalisme; Référendums

Women and Ethnic Language Maintenance: A Study of Italian Immigrant Family Triads in Saint-Léonard, Montréal - Venditti, Rosa L. (Université Concordia, 2003)
Keywords: Italiens; Langue; Quartiers; Saint-Léonard

Trajectoires et subjectivités italo-québécoises : le processus identitaire de la deuxième génération tel que conçu par Marco Micone, Mary Melfi et Paul Tana - Hélie-Martel, Anaïs (Université de Montréal, 2016)
Keywords: Cinéma; Italiens; Langue; Roman; Théâtre

Mille nuances pour un pays - Corriveau, Jeanne (Continuité, 2019)
issued: 2019-24-00
Keywords: Chinois; Conservation; Italiens; Patrimoine; Syriens

Le " Michel-Ange de Montréal ": Guido Nincheri - Grondin, Mélanie (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Arts sacrés; Italiens; Peinture; Vitraux; Églises

Invasion, Succession and Conflict: The Case of St. Leonard, Quebec - Smith, Courtney David Campbell (Pennsylvania State University, 1974)
Keywords: Francophones; Italiens; Saint-Léonard; Saint-Léonard (crise de)

Ethnic Political Participation in Montreal: the Role of Community Leaders - Lapp, Miriam (Université de Montréal, 1997)
Keywords: Chinois; Grecs; Italiens; Juifs; Portugais; Élections

Le boulevard Saint-Laurent dans la Petite-Italie: 1930, 1960 - Trépanier, Mathieu Alexandre (Université du Québec à Montréal, 2014)
Keywords: Italiens; Petite-Italie (quartier); Quartiers; Rues; Saint-Laurent (rue)

There's No Place Like Home: Feminist Communities, Social Citizenship and (Un)Belonging in Montreal's Long Women's Movement, 1952-1992 - Ricci, Amanda (Université McGill, 2015)
Keywords: Anglophones; Autochtones; Femmes; Francophones; Féminisme; Haïtiens; Italiens; Noirs

Témoins discrets - Leclerc, Jean-François (Continuité, 2019)
issued: 2019-24-00
Keywords: Chinois; Grecs; Irlandais; Italiens; Juifs; Noirs; Patrimoine; Syriens

La crise de Saint-Léonard dans la presse montréalaise, 1968-1969 - Chikli, Christophe (Université de Sherbrooke, 2006)
Keywords: Devoir (Le); Italiens; Langue; Montreal Gazette; Montreal Star; Presse (La); Saint-Léonard (crise de)

Les Communautés culturelles du Québec originaires de l'Europe centrale et de l'Europe du Sud - Lefebvre, Michel; Oryschuk, Yuri (Fides, 1985)
Keywords: Allemands; Autrichiens; Croates; Espagnols; Français; Grecs; Italiens; Portugais; Serbes; Slovènes; Suisses

Les banlieues de l'immigration ou quand les immigrants refont les banlieues - Germain, Annick; Rose, Damaris; Richard, Myriam (Histoire de Montréal et de sa région, 2012)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard

Building and Reshaping the Suburban Landscape: The Role of Immigrant Communities - Germain, Annick; Rose, Damaris; Richard, Myriam (Montreal: The History of A North American City, 2018)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard